MEMPERBESAR TENTARA CADANGAN PEKERJA: “BONUS DEMOGRAFI” DAN EKONOMI POLITIK NEGARA NEOLIBERAL DI INDONESIA - Arif Novianto (Universitas Gadjah Mada, 2017)
Demographic dividend which means that the amount of productive age (ages 15-65 years) has been interpreted by liberals as an opportunity for great improvement in the economy of a country. In a report from the World Bank, ILO and Bappenas said that the demographic dividend that occurred in Indonesia and reached its peak in 2035 is a golden bridge towards progress. This means that Indonesia if it is able to use it believed to be a country with high income and can transform into an industrial country. This paper seeks to elaborate on the structural condition of the emergence of the demographic dividend and associate it with the ASEAN Economic Community (AEC) which was implemented in 2015. Through analysis of the political economy of this paper will discuss about the problems faced by the reserve army of labour in relation to the neoliberal state. The findings of this paper is: 1) the impasse in the agrarian transformation process; 2) the demographic dividend entangled in the framework of the neoliberal state; 3) the reserve army of labour into specific mechanisms of capitalism in controlling wages and depoliticize the labor movement.